The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s12192-019-01043-6
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Arabidopsis’s heat shock factor HsfA1d mitigates adverse effects of heat stress on potato (Solanum tuberosum L.) plant

Abstract: Thermal stress induces a wide array of morphological and physiological changes in potato affecting its development and economic yield. Response to thermal stress in plants is mostly regulated by heat shock factors (hsfs). The current study aimed at improving heat tolerance by transforming potato plant with heat shock factor, HsfA1d, using Agrobacterium. Gateway cloning strategy was adopted for isolation of HsfA1d from Arabidopsis thaliana and cloning into plant expression vector. The target gene was introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Thus investigating the regulators that stabilize cellular metabolic processes in the thermotolerant plant is an efficient strategy for exploring the mechanisms underlying crop heat tolerance. Similar reports showed that the leaf angle and petiole length increased with temperature increase in Arabidopsis thaliana [49,50]. The photosynthetic systems of the two species of cucumber were damaged differently, which is common in crops.…”
Section: Changes In Cucumber Structure and Organization Under Heat St...supporting
confidence: 64%
See 1 more Smart Citation
“…Thus investigating the regulators that stabilize cellular metabolic processes in the thermotolerant plant is an efficient strategy for exploring the mechanisms underlying crop heat tolerance. Similar reports showed that the leaf angle and petiole length increased with temperature increase in Arabidopsis thaliana [49,50]. The photosynthetic systems of the two species of cucumber were damaged differently, which is common in crops.…”
Section: Changes In Cucumber Structure and Organization Under Heat St...supporting
confidence: 64%
“…Although constitutively expressed TFs may play crucial roles in regulating gene expression under high temperatures, heat stress-induced or heat-suppressed TFs in thermotolerant and thermosensitive plants potentially contribute to the differential regulation of downstream genes. HSF is one of the earliest reported and most studied transcription factors family related to heat stress regulation in plants, such as Arabidopsis [88,89], rice [90], tomatoes [91], and potatoes [50].…”
Section: Transcriptional Regulation Strategies After Heat Stress In C...mentioning
confidence: 99%
“…Reduced expression of most heat and many salt and H 2 O 2 -induced genes in QK mutant indicated that HSFA1 genes not only regulate heat tolerance, but control responses to other stresses also (Liu et al , 2011). On the other hand, overexpression of HSFA1 from different species conferred tolerance to several stresses including heat (Higashi, Ohama, Ishikawa, Katori, Shimura, Kusakabe, Yamaguchi-Shinozaki, Ishida, Tanaka, Seki, Shinozaki, Sakata, Hayashi & Taji, 2013, Lee, Hubel & Schoffl, 1995, Mishra et al , 2002, Shah, Shah, Ali, Munir, Khan, Iqbal, Ahmed & Jan, 2020, Zhu, Wang, Liu, Zhou, Yan, Yang & Shen, 2018, drought (Bechtold, Albihlal, Lawson, Fryer, Sparrow, Richard, Persad, Bowden, Hickman, Martin, Beynon, Buchanan-Wollaston, Baker, Morison, Schoffl, Ott & Mullineaux, 2013), oxidative treatments (Qian, Chen, Liu, Yang, Li & Zhang, 2014) or heavy metals (Cai, Zhang, Xu, Qi, Li, Ahammed, Xia, Shi, Zhou, Reiter, Yu & Zhou, 2017). HSFA1B overexpression promoted peroxide signaling and enhanced drought and heat tolerance in Arabidopsis and oilseed rape (Bechtold et al , 2013).…”
Section: Regulation Of Responses To Abiotic Stressesmentioning
confidence: 99%
“…The tripe and quadruple KO mutants were susceptible to multiple heat stress regimes, indicating that HsfA1a , HsfA1b and HsfA1d are the master regulators of heat stress response in Arabidopsis (Liu et al, 2011; Yoshida et al, 2011). HsfA1 genes from Thellungiella salsuginea and Brassica campestris could promote heat tolerance in Arabidopsis and tobacco, respectively (Higashi et al, 2013; Zhu et al, 2018; Shah et al, 2020), suggesting a conserved role of this gene family in heat tolerance. In addition to heat tolerance, HsfA1 genes are important for growth and responses to other environmental variations.…”
Section: Introductionmentioning
confidence: 99%